Using data projector in the methodology course class - T. Salman, Hawraa; Yusoff, Zailin Shah (Science Press, 2020)
This paper investigates the effect of using data projector in teaching "The methodology of English Language" course on the achievement of male students at Baghdad University in the 2018-2019 academic year. The sample of the study constituted 195 students who registered for the course. Both descriptive and inferential statistics were used for analysing participants' results. The results of the study indicated that all the study sample results were homogeneous and that there is a statistical difference in the students' achievement in a test in favour of the experimental group.